Examining Procrastination Across Multiple Goal Stages: A Longitudinal Study of Temporal Motivation Theory - Steel, Piers; Svartdal, Frode; Thundiyil, Tomas; Brothen, Thomas (Frontiers in Psychology, 2018)
Procrastination is among the most common of motivational failures, putting off despite expecting to be worse off. We examine this dynamic phenomenon in a detailed and realistic longitudinal design (Study 1) as well as in a large correlational data set (N = 7400; Study 2). The results are largely consistent with temporal motivation theory. People's pacing style reflects a hyperbolic curve, with the steepness of the curve predicted by self-reported procrastination. Procrastination is related to intention-action gaps, but not intentions. Procrastinators are susceptible to proximity of temptation and to the temporal separation between their intention and the planned act; the more distal, the greater the gap. Critical self-regulatory skills in explaining procrastination are attention control, energy regulation and automaticity, accounting for 74% of the variance. Future research using this design is recommended, as it provides an almost ideal blend of realism and detailed longitudinal assessment.